Law and the Contradictions of the Disability Rights Movement - Bagenstos, Samuel R. (Yale University Press, 2009)
The passage of the Americans with Disabilities Act in 1990 was hailed as revolutionary legislation, but in the ensuing years restrictive Supreme Court decisions have prompted accusations that the Court has betrayed the disability rights movement. The ADA can lay claim to notable successes, yet people with disabilities continue to be unemployed at extremely high rates. In this timely book, Samuel R. Bagenstos examines the history of the movement and discusses the various, often-conflicting projects of diverse participants. He argues that while the courts deserve some criticism, some may also be fairly aimed at the choices made by prominent disability rights activists as they crafted and argued for the ADA. The author concludes with an assessment of the limits of antidiscrimination law in integrating and empowering people with disabilities, and he suggests new policy directions to make these goals a reality.